Impact of prenatal exercise on both prenatal and postnatal anxiety and depressive symptoms: a systematic review and meta-analysis. Issue 21 (18th October 2018) - Davenport, Margie H; McCurdy, Ashley P; Mottola, Michelle F; Skow, Rachel J; Meah, Victoria L; Poitras, Veronica J; Jaramillo Garcia, Alejandra; Gray, Casey E; Barrowman, Nick; Riske, Laurel; Sobierajski, Frances; James, Marina; et al.
Abstract : Objective: To examine the influence of prenatal exercise on depression and anxiety during pregnancy and the postpartum period. Design: Systematic review with random effects meta-analysis and meta-regression. Data sources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were included (except case studies) if they were published in English, Spanish or French and contained information on the Population (pregnant women without contraindication to exercise), Intervention (subjective or objective measures of frequency, intensity, duration, volume or type of exercise), Comparator (no exercise or different frequency, intensity, duration, volume and type of exercise) and Outcome (prenatal or postnatal depression or anxiety). Results: A total of 52 studies (n=131 406) were included. 'Moderate' quality evidence from randomised controlled trials (RCTs) revealed that exercise-only interventions, but not exercise+cointerventions, reduced the severity of prenatal depressive symptoms (13 RCTs, n=1076; standardised mean difference: −0.38, 95% CI −0.51 to –0.25, I 2 =10%) and the odds of prenatal depression by 67% (5 RCTs, n=683; OR: 0.33, 95% CI 0.21 to 0.53, I 2 =0%) compared with no exercise. Prenatal exercise did not alter the odds of postpartum depression or the severity of depressive symptoms, nor anxiety or anxiety symptoms during or following pregnancy. To achieve at least a moderate effect size in the reduction of the severity of prenatal depressive symptoms, pregnant women needed to accumulate at least 644 MET-min/week of exercise (eg, 150 min of moderate intensity exercise, such as brisk walking, water aerobics, stationary cycling, resistance training). Summary/Conclusions: Prenatal exercise reduced the odds and severity of prenatal depression.